Influence of Comorbidities and Airway Clearance on Mortality and Outcomes of Patients With Severe Bronchiectasis Exacerbations in Taiwan - Huang, Hung-Yu; Chung, Fu-Tsai; Lin, Chun-Yu; Lo, Chun-Yu; Huang, Yu-Tung; Huang, Yu-Chen; Lai, Yu-Te; Gan, Shu-Ting; Ko, Po-Chuan; Lin, Horng-Chyuan; Chung, Kian Fan; Wang, Chun-Hua (Frontiers in Medicine, 2022)
Bronchiectasis is characterized by systemic inflammation and multiple comorbidities. This study investigated the clinical outcomes based on Bronchiectasis aetiology comorbidity index (BACI) score in patients with bronchiectasis hospitalized with pneumonia.We included patients with non-cystic fibrosis bronchiectasis hospitalized for pneumonia between January 2008 and December 2016 using the Chang Gung Research Database cohort. The main outcome was 1-year mortality rate after hospitalization for pneumonia. We used the Cox regression model to assess the risk factors of 1-year mortality. Of 1,235 patients with bronchiectasis hospitalized for pneumonia, 641 were in the BACI<6 and 594 in the BACI ≥ 6 group. The BACI ≥ 6 group had more previous exacerbations and a lower FEV1. Pseudomonas aeruginosa (19.1%) was the most common bacteria, followed by Klebsiella pneumoniae (7.5%). Overall, 11.8% patients had respiratory failure and the hospital mortality was 3.0%. After discharge, the BACI ≥ 6 group had significantly higher cumulative incidence of respiratory failure and mortality than BACI<6 group at 1-year follow-up. The risk factors for 1-year mortality by multivariate analysis include age (hazard ratio (HR) 4.38, p=0.01), being male (HR 4.38, p=0.01), and systemic corticosteroid usage (HR 6.35, p=0.001), while airway clearance therapy (ACT) (HR 0.50, p=0.010) was associated with a lower risk of mortality. Bronchiectasis patients with multi-morbidities had an increased risk of respiratory failure and mortality at 1-year follow up after hospitalization for pneumonia, especially in older age, being male and systemic corticosteroid use. ACT could effectively improve the risk for 1-year mortality.